PENGARUH PEMANFAATAN DIGITAL MARKETING DAN CELEBRITY ENDORSEMENT TERHADAP MINAT MENABUNG NASABAH PADA BANK SYARIAH (Studi Pada Nasabah Bank BSI Kabupaten Bone) - Sinta Sahara; Abd.Hafid; Sitti Nikmah Marzuki (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study aims to determine the effect of the use of digital marketing and the influence of celebrity endorsement on customer savings interest at the BSI bank, Bone branch. The variables used in this study are the dependent variables whether digital marketing and celebrity influence customer savings interest. This study uses a quantitative research method. The data for this study uses primary data by distributing questionnaires to 70 BSI customer respondents in Bone Regency. The sampling technique uses simple random sampling. The data processing for this study uses SPSS software version 29. The results of this study indicate that (1) Utilization of Digital Marketing has a positive and significant effect on Customer Saving Interest. (2) Utilization of Celebrity Endorsement has a positive and significant effect on Customer Saving Interest (3) The value of the coefficient of determination shows that the variables digital marketing and Celebrity Endorsement have an influence of 31.1% while the remaining 68.9% is influenced by other variables not used in this study